Factors associated with anxiety, depression and occurrence of violence in elderly people resident in the urban area of Araguari, state of Minas Gerais (MG), Brazil (Research, Society and Development, 2024)
Introduction: Population aging is a natural and global phenomenon, requiring better access opportunities for the elderly in social, cultural, physical, and psychological areas. Objectives: This study aims to estimate the prevalence of psychological problems and violence among the elderly in Araguari-MG and compare the impacts of these conditions concerning adverse effects. Methodology: An observational, analytical, cross-sectional, and quantitative methodology was used, with a random sample of 376 elderly individuals analyzed through semi-structured questionnaires. Results: The research indicated a high prevalence of anxiety (24.3%) and depression (14.1%), with significant associations between these disorders and adverse events such as insomnia and sensory impairments. Domestic violence was identified in 2.5% of cases, revealing the need for interventions focused on the mental health and well-being of the elderly. Conclusion: The study concludes that there is an urgent need for comprehensive public policies and a multifactorial approach, guided by the principles of the Brazilian Unified Health System (SUS), to promote aging with quality of life.